Pengaruh Pemasaran Media Sosial Instagram terhadap Minat Beli pada Respiesusu Lampung Selatan - Ratih Murti Dewi; Suhartina Dewi; Suryani Dewi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2026)
Social media marketing plays an important role for business actors in expanding market reach and attracting consumer buying interest. One of the most widely used social media platforms for promotional activities is Instagram, due to its ability to display engaging visual content and reach a broad audience. This study aims to determine the influence of Instagram social media marketing on consumer buying interest in Respiesusu culinary products in South Lampung. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 86 respondents who were Respiesusu consumers, using a purposive sampling technique. The data were analyzed using simple linear regression analysis to test the research hypothesis. The results show that Instagram social media marketing has a significant influence on consumer buying interest in Respiesusu. This is evidenced by the value of t_calculated = 5.816 > t_table = 1.663 and an R Square value of 0.287 or 28.7%. This means that Instagram social media marketing contributes 28.7% to consumer buying interest, while the remaining percentage is influenced by other factors. Thus, it can be concluded that Instagram social media marketing is an important factor in increasing consumer buying interest in Respiesusu South Lampung. Keywords: instagram, marketing, purchase intention, social media